Public Sector Wage Policy and Labor Market Equilibrium: A Structural Model. Issue 6 (14th February 2017) - Bradley, Jake; Postel-Vinay, Fabien; Turon, Hélène
Abstract: We develop and estimate a structural model that incorporates a sizeable public sector in a labor market with search frictions. The wage distribution and the employment rate in the public sector are taken as exogenous policy parameters. Overall wage distribution and employment rate are determined within the model, taking into account the private sector's endogenous response to public sector employment policies. Job turnover is sector specific and transitions between sectors depend on the worker's decision to accept alternative employment in the same or different sector by comparing the value of employment in the current and prospective jobs. The model is estimated on British data by a method of moments. We use the model to simulate the impact of various counterfactual public sector wage and employment policies.